FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS PENGRAJIN MEUBEL ROTAN DI DESA TRANGSAN KECAMATAN GATAK KABUPATEN SUKOHARJO - Suwarto Suwarto; Syamsudin Syamsudin (Jurnal Manajemen Dayasaing, 2015)
This study analylizes the influence wages and working experience on the productivity ofrattan furniture craftsmen in the village Trangsan Gatak District of Sukoharjo district. The population of this study were 170 craftsmen. While the study sample was 62 respondents. This study uses a random sampling technique. The results of multiple linear regression analysis showed no effect of dominant work experience. Hypothesis test results showed a significant influence on the productivity of craftsmen and work experience. The results of hypothesis testing is influenced by other factors, such as factors of discipline, safety, and security.